2017
DOI: 10.1016/j.drugalcdep.2017.06.037
|View full text |Cite
|
Sign up to set email alerts
|

The association between parental history and delay discounting among individuals in recovery from addiction

Abstract: Background Family history of addiction is a risk factor for substance use disorders. Delay discounting (DD) is associated with the risk of substance use and dependence, and is predictive of the likelihood of successful abstinence and treatment outcomes; thus, we investigated the extent to which having parents with addiction (parental history of addiction) and number of addicted parents affect DD among individuals in recovery from addiction. Methods Data from 177 individuals in recovery from addiction from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Numerous studies have shown that the decline in the reward value is not only significantly steeper in addicted individuals compared with their non-drug-using peers [88], but the steepness of decline varies across different drug classes [87]. Choice preference has also been shown to persist during early abstinence [109], which is consistent with the notion of delay discounting being a heritable trait [110][111][112], which may be further exacerbated by chronic substance abuse [113]. However, whether or not delay discounting actually represents an endophenotype for addiction is still unclear.…”
Section: Studies In Humans (A) Impulsivity and Addiction Vulnerabilitymentioning
confidence: 61%
“…Numerous studies have shown that the decline in the reward value is not only significantly steeper in addicted individuals compared with their non-drug-using peers [88], but the steepness of decline varies across different drug classes [87]. Choice preference has also been shown to persist during early abstinence [109], which is consistent with the notion of delay discounting being a heritable trait [110][111][112], which may be further exacerbated by chronic substance abuse [113]. However, whether or not delay discounting actually represents an endophenotype for addiction is still unclear.…”
Section: Studies In Humans (A) Impulsivity and Addiction Vulnerabilitymentioning
confidence: 61%
“…It may also predispose one to a SUD (Poulton & Hester, 2020). Similar to risk of relapse, delay discounting is associated with individual characteristics and demographic variables including age (Steinberg et al, 2009), education (Jaroni et al, 2004), polysubstance use (Moody et al, 2016), family history of substance misuse (Athamneh et al, 2017a; VanderBroek et al, 2015), abstinence self‐efficacy (Athamneh et al, 2019), intention to quit (Athamneh et al, 2017b), and depression scores (García‐Pérez et al, 2020; Imhoff et al, 2014). Longer time in recovery is associated with lower rates of discounting (Athamneh et al, 2019; Tomlinson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to examine the relationship of age to these variables within our sample, as age is a construct related to recovery from substance use disorders as demonstrated by the phenomena of maturing out of addiction ( Vergés et al, 2013 , Waldorf, 1983 , Waldorf and Biernacki, 1981 ). Data from these measures and demographic characteristics were collected from the International Quit and Recovery Registry (IQRR) ( http://quitandrecovery.org ), an online community designed to further understand the phenotype of recovery (see also Athamneh et al, 2019 , Athamneh et al, 2017 ). We hypothesized that higher rates of discounting would be associated with higher levels of perceived stress, higher scores regarding beliefs about external locus of control (measured by the IPCS and the DRLOC), and a shorter time in self-reported recovery.…”
Section: Introductionmentioning
confidence: 99%